МЕХАНИЗМЫ ПОВРЕЖДЕНИЯ МИКРОЦИРКУЛЯТОРНОГО РУСЛА И СОЕДИНИТЕЛЬНОТКАННЫХ СТРУКТУР ПРИ ПСОРИАЗЕ - Тошев, Сухроб Уктамжон угли; Абдуллаев , Хасан Давлатович; Маматов, Жахонгир Мавлонович (Educational Research in Universal Sciences, 2024)
The scientific article examines the mechanisms of damage to the microvasculature and connective tissue structures in psoriasis, a chronic inflammatory skin disease. The study focuses on complex aspects of pathogenesis, including inflammatory and immune mechanisms, activation of T lymphocytes and dendritic cells, and the role of cytokines. Clarification of these mechanisms is key to understanding the impact of psoriasis on microcirculatory status and connective tissue structure. The literature review also covers current scientific advances, providing insights into potential targets for innovative treatment and management strategies for this common dermatological disease. Understanding these mechanisms contributes not only to an in-depth knowledge of psoriasis, but also to the formation of the basis for new approaches to therapy.